If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6g + 27 = 36 Reorder the terms: 27 + 6g = 36 Solving 27 + 6g = 36 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 6g = 36 + -27 Combine like terms: 27 + -27 = 0 0 + 6g = 36 + -27 6g = 36 + -27 Combine like terms: 36 + -27 = 9 6g = 9 Divide each side by '6'. g = 1.5 Simplifying g = 1.5
| y+63=8y | | (x-7)(-1)=0 | | .08=.03+.60*.05 | | 10y=21+7y | | .08=.03+.03 | | 3x+5=2(2x-1)1-(x-3) | | -3/5c-7=6 | | 227=142-u | | 18m+9=3(4m-9) | | (x-7)(4)=0 | | 23-x=275 | | -0.6c-7=6 | | 3-5x-7x=87 | | 14x-3=9x+5 | | 168=19-v | | 2+e=-2 | | ln(5x)+ln(10x)= | | 3(5x+3)=-5(5x-2) | | v+60=5v | | 3x+90=126 | | 6x=9y-6 | | 0.6(b-4)=-9 | | 8x-2y=41 | | 1.82= | | x(x+12)=(x-4)(x-4) | | ln(5x)+ln(10x)=4 | | 4-v=265 | | 6x+9y=65 | | Y-4+7y=24 | | -16=-4+4y | | y-7.2=9 | | 8x-(11x-9)=24-3x |